2007
DOI: 10.1007/s11104-007-9291-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the effects of three arbuscular mycorrhizal fungal strains on P and Pb accumulation by maize plants

Abstract: The effect of arbuscular mycorrhizal (AM) fungi on the accumulation and transport of lead was studied in a pot experiment on maize plants grown in anthropogenically-polluted substrate. The plants remained uninoculated or were inoculated with different Glomus intraradices isolates, either indigenous to the polluted substrate used or reference from non-polluted soil. A considerably lower tolerance to the conditions of polluted substrate was observed for the reference isolate that showed significantly lower frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 29 publications
7
21
2
Order By: Relevance
“…Maize has been shown to respond positively in terms of growth and nutrition to isolates of G. intraradices (e.g., Mickelson and Kaeppler 2005;Sudova and Vosatka 2007), but in our study the inoculant G. intraradices did not affect the host's P content in absence of the resident AM fungal community. This further supports that host-plant responses to individual AM isolates may vary depending on the isolate's interactions with other AM fungi (Gustafson and Casper 2006) in combination with environmental factors (Smith and Smith 1996;Johnson et al 1997).…”
Section: Discussioncontrasting
confidence: 67%
“…Maize has been shown to respond positively in terms of growth and nutrition to isolates of G. intraradices (e.g., Mickelson and Kaeppler 2005;Sudova and Vosatka 2007), but in our study the inoculant G. intraradices did not affect the host's P content in absence of the resident AM fungal community. This further supports that host-plant responses to individual AM isolates may vary depending on the isolate's interactions with other AM fungi (Gustafson and Casper 2006) in combination with environmental factors (Smith and Smith 1996;Johnson et al 1997).…”
Section: Discussioncontrasting
confidence: 67%
“…Sudova and Vosatka (2007) have also concluded that the inoculation of various isolates/ecotypes of the AM fungus, G. intraradices, resulted in a higher tolerance and biomass production of maize plants under Pb stress. All of these results are in agreement with the results obtained in the present study, in which the M plants exhibited a better performance in Pb-contaminated soils than the NM plants, confirming that the accumulation of biomass is a function of AM association.…”
Section: Discussionmentioning
confidence: 98%
“…Even though there is little available literature regarding the effect of Pb in the Ca content in plants, the results of our study are in accordance with those found by Andrade et al (2003), which have shown that Pb did not cause a reduction in the Ca concentration in soybeans plants, independent of its mycorrhizal status. In a general manner, it was evident that mycorrhization exerted a positive influence in the absorption of certain nutrients, such as Fe, P and S. Sudova and Vosatka (2007) have observed that maize plants associated with G. intraradices in Pb-contaminated soil absorbed lower Pb than non-AM associated plants, whereas Chen et al (2005) have observed that the plants used in their study, grown in Pb-contaminated soil, absorbed more Pb when they were colonized by AM fungi. Because we observed no differences in Pb transportation to the aerial parts up to the moderate Pb dose (500 mg kg -1 ) and a repression of this transportation at the highest Pb dose (1,000 mg kg -1 ), we hypothesize that this feature is likely dependent of the plant and fungus species.…”
Section: Discussionmentioning
confidence: 98%
“…Concentration of heavy metals, e.g. lead, and P in maize plants generally increases when inoculated with arbuscular mycorrhizal fungi, which suggest significant participation of fungal structures in element accumulation (Sudova and Vosatka, 2007). A previous work established that improved P nutrition at early stages of maize growth is reflected in the final maize yield (Gavito and Miller, 1998).…”
Section: Qualitative Parametersmentioning
confidence: 93%